Regional Women’s Economic Participation: A Systematic-based Review of Structural Economic Transformation in Indonesia - Endah Prihatiningtyastuti (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2020)
This article draws upon available works of literature to argue that the regional women’s economic participation in structural economic transformation in Indonesia has been challenged continuously by cultural and structural factors. This reviewed article aims at providing several scientific publications on a related topic to map the available sources in understanding the contribution of women in the economic sector as well as the challenges they faced. This review paper employs a qualitative method with a systematic review of certain works related to women’s participation in the economic sector. This review paper aims to provide a conceptual framework and navigation for further research conducted in a related field study. This article also synthesising an overview of the current study. By analysing reports, statistics, and prior works on this women’s participation and transition into formal employment issues, this article finds Indonesian women are still less involved in the labour force and labour market than men. Socio-cultural and structural barriers contribute to the low participation of women in the economy. Such barriers include career interruption of childbirth and childcare responsibility, less education and skills, care services that the women involved considered secondary, low wage, unsupported gender-based regulations, and low support to gender equality.